Egirdira, a new generic name for Pararhodeus niger Kosswig & Geldiay, 1952 (Teleostei: Leuciscidae) - Freyhof, Jörg (Zootaxa, 2022)
Egirdira, new genus, is proposed for Pararhodeus niger from Central Anatolia based on its position in molecular phylogenetic analyses and its morphological characters. It is distinguished from all other genera of Leuciscidae except Delminichthys and Pelasgus by having the unbranched part of pectoral rays 2–3 thickened and slanted upward, with a conspicuous downward angle at the distal end of the thickened part, no or an incomplete lateral line, and the genital papilla of the female not protruding. An unambiguous, unique morphological character distinguishing Egirdira from Pelasgus has not been identified, except that Egirdira has numerous isolated silvery scales (or patches of such scales) on the flank. A combination of characters distinguishes Egirdira from individual species of Pelasgus. Phoxinellus egridiri is a junior synonym of Pararhodeus niger.